2005
DOI: 10.4049/jimmunol.174.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Murine CTL by a Hepatitis B Virus-Specific Peptide and Evaluation of the Adjuvant Effect of Heat Shock Protein Glycoprotein 96 and Its Terminal Fragments

Abstract: Previously, we reported that a 7-mer HLA-A11-restricted peptide (YVNTNMG) of hepatitis B virus (HBV) core Ag (HBcAg88–94) was associated with heat shock protein (HSP) gp96 in liver tissues of patients with HBV-induced hepatocellular carcinoma (HCC). This peptide is highly homologous to a human HLA-A11-restricted 9-mer peptide (YVNVNMGLK) and to a mouse H-2-Kd-restricted 9-mer peptide (SYVNTNMGL). To further characterize its immunogenicity, BALB/c mice were vaccinated with the HBV 7-mer peptide. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 47 publications
3
65
0
Order By: Relevance
“…Immunization with P15 and an adjuvant elicited a substantial quantity of specific cytotoxic CD8 ϩ T lymphocytes that could be used to assess the function of cellular immunity in protection and clearance of SARS-CoV. Using the N-terminal fragment N334 of GP96 with IFA seems to be especially wellsuited for this purpose (49). This immune method can also be practiced easily and effectively in testing immunogenicity of potential CTL epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization with P15 and an adjuvant elicited a substantial quantity of specific cytotoxic CD8 ϩ T lymphocytes that could be used to assess the function of cellular immunity in protection and clearance of SARS-CoV. Using the N-terminal fragment N334 of GP96 with IFA seems to be especially wellsuited for this purpose (49). This immune method can also be practiced easily and effectively in testing immunogenicity of potential CTL epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the in vivo immunogenic potential of peptide P15, we immunized HLA-A2.1/K b transgenic mice with peptide P15, using IFA and the N-terminal fragment N334 (22-355aa) of murine GP96 as an adjuvant (49). After three rounds of weekly in vivo stimulation, splenocytes from primed mice were tested for IFN-␥ production and chimeric HLA-A*0201 tetramer staining.…”
Section: In Vivo Induction Of Peptide-specific Ctls In Hla-a21/k B -mentioning
confidence: 99%
“…49 Even, the reports on the adjuvant activity of C-terminal domain of gp96 are controversial, depending on the antigen. 50,51 The data showed that the construct containing the C-terminal of gp96 fused with Her2/neu, but not the co-administration of the two separated constructs, decreased CD4+CD25+foxp3+ regulatory T cells at the tumor site and enhanced CTL activity as well as IFN-γ secretion. Therefore, the C-terminal of gp96 can be used as molecular adjuvant along with other tumor/ bacterial/viral antigens for improving vaccine potency.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%
“…58 Lipophosphoglycan 3 (LPG3), the Leishmania homologous with Gp96, is involved in assembly of LPG as the most abundant might induce an innate immune response to produce an immunological environment optimal for adequate peptide quantities to be cross-presented. 75 …”
Section: Protein/peptide-based Vaccinementioning
confidence: 99%
See 1 more Smart Citation